XRD Characterization and Structural Insights of Activated Carbon-ZnO Composite for Potential Photocatalytic Applications - Lestari, Devi; Masriah, Imas; Hasibuan, Adelia Yesya Putri; Pratiwi, Pina Budiarti (Jurnal Beta Kimia, 2025)
This study presents a structural characterization of an activated carbon-ZnO (AC/ZnO) composite synthesized via a simple sol-gel route using activated carbon derived from oil palm empty fruit bunches (OPEFB), introducing a sustainable biomass based carbon source as a functional photocatalytic support. X-ray diffraction (XRD) analysis revealed sharp diffraction peaks corresponding to the wurtzite ZnO phase, together with a broad amorphous carbon halo, confirming the successful incorporation of crystalline ZnO within the carbon matrix. Microstructural parameters, including crystallite size, lattice strain, and dislocation density, indicate nanoscale structural ordering accompanied by beneficial defect sites that promote charge trapping. Structural interpretation was further validated through Rietveld refinement, which confirmed a single-phase ZnO structure with good fitting quality, demonstrating the structural stability and compatibility of ZnO within the carbon framework. Photocatalytic evaluation using methylene blue showed a higher removal efficiency under natural sunlight (95%) compared to dark adsorption (85%), evidencing a synergistic adsorption-photocatalysis mechanism. The novelty of this work lies in integrating low temperature sol–gel synthesis, waste derived activated carbon, and XRD based microstrain and refinement analyses to establish a clear structure–function relationship in AC/ZnO composites. These findings highlight the practical potential of this material as a low cost, scalable, and solar responsive photocatalyst for sustainable wastewater treatment applications, particularly in resource limited and tropical regions.